Deciphering the role of platelets in severe allergy by an integrative omics approach. Issue 5 (12th January 2023) - Pablo‐Torres, Carmela; Izquierdo, Elena; Tan, Tiak Ju; Obeso, David; Layhadi, Janice A.; Sánchez‐Solares, Javier; Mera‐Berriatua, Leticia; Bueno‐Cabrera, José Luis; del Mar Reaño‐Martos, María; Iglesias‐Cadarso, Alfredo; Barbas, Coral; Gomez‐Casado, Cristina; et al.
Abstract: Background: Mechanisms causing the onset and perpetuation of inflammation in severe allergic patients remain unknown. Our previous studies suggested that severe allergic inflammation is linked to platelet dysfunction. Methods: Platelet‐rich plasma (PRP) and platelet‐poor plasma (PPP) samples were obtained by platelet‐apheresis from severe ( n = 7) and mild ( n = 10) allergic patients and nonallergic subjects ( n = 9) to perform platelet lipidomics by liquid chromatography coupled to mass spectrometry (LC–MS) and RNA‐seq analysis. Significant metabolites and transcripts were used to identify compromised biological pathways in the severe phenotype. Platelet and inflammation‐related proteins were quantified by Luminex. Results: Platelets from severe allergic patients were characterized by high levels of ceramides, phosphoinositols, phosphocholines, and sphingomyelins. In contrast, they showed a decrease in eicosanoid precursor levels. Biological pathway analysis performed with the significant lipids revealed the alteration of phospholipases, calcium‐dependent events, and linolenic metabolism. RNAseq confirmed mRNA overexpression of genes related to platelet activation and arachidonic acid metabolism in the severe phenotypes. Pathway analysis indicated the alteration of NOD, MAPK, TLR, TNF, and IL‐17 pathways in the severe phenotype. P‐Selectin and IL‐17AF proteins were increased in the severe phenotype. Conclusions: This study demonstrates that platelet lipid, mRNA, and protein content is different according to allergy severity. These findings suggest that platelet load is a potential source of biomarkers and a new chance for therapeutic targets in severe inflammatory pathologies. Abstract : This study analyzes the lipidomic and transcriptomic profile of platelets in patients with mild and severe allergy. The lipidomic profile of platelets form severe allergic patients shows high levels of ceramides, phosphoinositols, phosphocholines, and sphingomyelins and low levels of arachidonic acid. Transcriptomics reveals a higher expression of platelet activation genes and the alteration of IL‐17, MAPK, TLR, and NLR pathways in the severe phenotype, which was validated by P‐Selectin and IL‐17 AF protein quantification.Abbreviations: ALOX12, arachidonate 12‐lipoxygenase; CD40L, CD40 ligand; CPM, counts per millon; IL, interleukin; ITGB3, integrin subunit beta 3; −Log(P), −Logarithm in base 10 of P value; MAPK, mitogen‐activated protein kinase; NLR, NOD‐like receptor; PPBP, pro‐platelet basic protein; SELP, selectin P; TLR, Toll‐like receptor